2012
DOI: 10.1007/7854_2012_206
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Protocols for Behavioral Imaging: Seeing Animal Models of Drug Abuse in a New Light

Abstract: Behavioral neuroimaging is a rapidly evolving discipline that represents a marriage between the fields of behavioral neuroscience and preclinical molecular imaging. This union highlights the changing role of imaging in translational research. Techniques developed for humans are now widely applied in the study of animal models of brain disorders such as drug addiction. Small animal or preclinical imaging allows us to interrogate core features of addiction from both behavioral and biological endpoints. Snapshots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Importantly, a recent study showed that light delivery in the absence of optogenetic stimulation induced strong local fMRI responses in the stimulated site (3). To overcome these limitations, we combined designer receptor exclusively activated by designer drug (DREADD) technology (4), which allows remote in vivo control of cell-specific firing (5), together with behavioral imaging using μPET and [ 18 F]fluorodeoxyglucose (FDG) to measure regional brain glucose metabolism, which is a direct marker of brain function (6)(7)(8)(9). This approach, termed DREADD-assisted metabolic mapping (DREAMM), was used to map functional brain anatomy associated with inhibiting the activity of prodynorphin-expressing (Pdyn-expressing) and of proenkephalin-expressing (Penk-expressing) medium spiny neurons (MSNs) in the medial nucleus accumbens shell (NAcSh), highly implicated in neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a recent study showed that light delivery in the absence of optogenetic stimulation induced strong local fMRI responses in the stimulated site (3). To overcome these limitations, we combined designer receptor exclusively activated by designer drug (DREADD) technology (4), which allows remote in vivo control of cell-specific firing (5), together with behavioral imaging using μPET and [ 18 F]fluorodeoxyglucose (FDG) to measure regional brain glucose metabolism, which is a direct marker of brain function (6)(7)(8)(9). This approach, termed DREADD-assisted metabolic mapping (DREAMM), was used to map functional brain anatomy associated with inhibiting the activity of prodynorphin-expressing (Pdyn-expressing) and of proenkephalin-expressing (Penk-expressing) medium spiny neurons (MSNs) in the medial nucleus accumbens shell (NAcSh), highly implicated in neuropsychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, retrospective evaluations of animal disease models indicate the utility of frameworks which explicitly create avenues for researchers to synthesize findings and provide continuity across subfields [16][17][18][19][20][21]. In the absence of purposeful development of methodological solutions, there is a natural tendency for fields to split along basic and translational lines as highly specialized paradigms are pushed towards partially divergent goals: basic investigations require flexibility of experimental design as hypotheses are rapidly tested and revised, while animal models intended for preclinical to clinical translation emphasize standardized protocols to allow comparison of specific outcome measures [22,23]. The tendency for basic experimental studies and preclinical testing to use non-overlapping methodologies, without explicit efforts to integrate conclusions, impedes progress and translation [18,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%